The challenge of the contribution of the amazon cooperation treaty organization — acto — to the wellbeing of local populations on the border (2013)
This paper addresses the description of social, economic and political dynamics of the Amazonian populations living in border regions, amidst conflictual situations, and different degrees of presence of the nation-states and their institutions. The paper depicts the policies of multilateral organisms, such as acto, which have as objective the formulation of plans and strategic agendas for sustainable development and the use and conservations of Amazon natural systems and resources. The central argument is that these policies, plans and programs have a minimal impact in solving the problems and conflicts that Amazonian local populations face, given the absence of instruments that allow for the articulation of the broad formulations of the policies with the concrete proposals and projects to attain a sustainable development and better living conditions for these populations